Effect of alkali concentration on mechanical properties of kaolin geopolymers - Heah, Cheng Yong; Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr.; Mohd Mustafa Al Bakri, Abdullah; Mohammed, Husain; Luqman, Musa; Khairul Nizar, Ismail; Liew, Yun Ming (Foundation for Materials Science and Engineering, 2013)
Link to publisher's homepage at http://solacolu.chim.upb.ro/